Biogeography and systematics of the genus Axyris (Amaranthaceae s.l.) - Sukhorukov, Alexander P.; Shiposha, Valeria D.; Kushunina, Maria A.; Zaika, Maxim A. (Plants)
Axyris is a small genus of six species with a disjunct geographic range. Five species are present in Siberia, Central Asia, the Himalayas, and Tibet, whereas Axyris caucasica has been registered in the Central Caucasus only. Axyris species diversity is the highest in the Altai Mountains (four spp.), followed by the Tian Shan and Pamir Mountains (three spp.), and the Himalayas and Tibet (two spp.). Axyris sphaerosperma, sometimes considered endemic to Southern Siberia, in fact has a disjunct range: it is present in the lowlands of Eastern Siberia and in the Altai, Tian Shan, and Pamir Mountains. It has also been found in Mongolia and China for the first time. An updated detailed distribution of Axyris in Siberia is presented on the basis of thorough herbarium revisions. One nuclear and three plastid markers were selected for phylogenetic analysis. Divergence times were estimated using a time-calibrated Bayesian approach. Axyris shows two major clades: an Axyris amaranthoides clade and a clade including the remaining species. The latter clade consists of two subclades (A. sphaerosperma/A. caucasica and A. mira/A. prostrata + A. hybrida). The crown age for Axyris dates back to the Early Pliocene (similar to 5.11 mya, the Zanclean). The ancestral range of Axyris covers Southern Siberia, Mongolia, NW China, and the Tian Shan/Pamir Mountains, with extensions toward Eastern Siberia, the Himalayas/Tibet, and the Caucasus. Fruit and seed characteristics of Axyris are discussed with reference to the present phylogenetic results. Closely related A. sphaerosperma and A. caucasica have the thickest seed coat among all Chenopodiaceae, and these traits have probably evolved as adaptations to extremely low winter temperatures. This reproductive peculiarity may explain the disjunct range of A. sphaerosperma, which is restricted to harsh climatic conditions.